(untitled) (Journal of Hama University, 2024)
Diabetes mellitus has been identified as one of the leading systemic risk factors for dry eye syndrome Methods : This study was conducted on 100 patients diabetics, 40 patients type I and 60 patients type II, the age was between 15-75 years , all patients underwent a general ophthalmological check-up for retina and HbAIc and some special tests of dry eye syndrome was assessed with Tear film break up time ,schirmer test and questionnaire OSDI . Results: we found that 55% of patients type II and 44% type I suffered from dry eye syndrome ,a correlation was found between the HbA1c and the presence of dry eye syndrome ,the higher the HbA1c values the higher rate of dry eye syndrome . Conclusion: The study thus supports the impression that diabetic patients have an elevated incidence of dry eye syndrome,. more than 70% of patients had HbA1c was above 8,5 mg ,and we found that more than 90% of patients above 45 years ,which indicated that increasing age increases the incidence of dry eye.